Lawrence Halprin - Helphand, Kenneth I. ca. 20.Jh- (Masters of modern landscape design, 2017)
During a career spanning six decades, Lawrence Halprin (1916-2009) became one of the most prolific and outspoken landscape architects of his generation. He took on challenging new project types, developing a multidisciplinary practice while experimenting with adaptive reuse and ecological designs for new shopping malls, freeways, and urban parks. In his lifelong effort to improve the American landscape, Halprin celebrated the creative process as a form of social activism. A native New Yorker, Halprin earned degrees from Cornell and the University of Wisconsin before completing his design degree at Harvard. In 1945 he joined Thomas Church's firm, where he collaborated on the iconic Donnell Garden. He opened his own San Francisco office in 1949, where he initially focused on residential commissions in the Bay Area, completing close to three hundred in ten years' time. By the 1960s the firm had gained recognition for significant urban renewal projects such as Ghirardelli Square in San Francisco (1962-68), Nicollet Mall in Minneapolis (1962-67), and Freeway Park in Seattle (1970-74). Halprin used his conception of a Sierra stream as the catalyst for the Portland Open Space Sequence, a series of parks featuring great fountains that linked housing and civic space in the inner city. A charismatic speaker and passionate artist, Halprin designed landscapes that reflected the democratic and participatory ethic characteristic of his era. He communicated his ideas as well in lectures, books, exhibits, and performances. Along with his contemporary Ian McHarg, Halprin was his generation's great proselytizer for landscape architecture as environmental design. Throughout his long career, he strived to develop poetic and symbolic landscapes that, in his words, could "articulate a culture's most spiritual values."